1997
DOI: 10.1007/bf01358737
|View full text |Cite
|
Sign up to set email alerts
|

Rib-vertebral angle asymmetry in idiopathic, neuromuscular and experimentally induced scoliosis

Abstract: The concave and convex rib-vertebral angle (RVA) at levels T2-T12 was measured on AP radiographs of 19 patients with right convex idiopathic thoracic scoliosis and 10 patients with major thoracic right convex neuromuscular scoliosis. The difference between the angles on the concave and the convex sides, the RVAD, was calculated. The RVAs were also measured on radiographs from three animal groups in which spinal curves had been induced experimentally in a variety of ways. Group 1 comprised 16 rabbits that had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…1). Our data differ from those published by Sevastik et al [4] probably due to different curve patterns.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…1). Our data differ from those published by Sevastik et al [4] probably due to different curve patterns.…”
Section: Discussioncontrasting
confidence: 99%
“…For this reason, we decided to include patients of the same gender with similar curve patterns. Sevastik et al [4], Kristmundsdottir et al [6], Modi et al [7], Xiong et al [15], and Burwell et al [19] showed that RVADs increase linearly with a wider Cobb angle, convex apical RVA is as important as apical RVAD, and RVADs are largest at two and three vertebral levels above the apex where they correlate significantly and positively with the Cobb angle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in all groups the rib-vertebra angles (RVAs) of the convex and the concave side of the scoliotic curvature were measured on radiographs from level T1 to T8 as described previously by Mehta [24] and Sevastik et al [28], and the difference between the two, the RVAD (RVA concave-RVA convex), was then calculated for differentiation between progressive and regressive scoliosis. The mean RVAD for each group was calculated, and these values were used for the analysis.…”
Section: Rib-vertebra Anglementioning
confidence: 99%